Would and Used to as Markers of Modality and Habituality in English Language - Babić Antić, Jelena B.; Spasić, Dragana M. (Collection of Papers of the Faculty of Philosophy in Priština, 2017)
This paper gives an insight into habitualness in English language. It explains that simple tenses, modals used to and would are traditionally considered to ne markers of Habituality. According to Bernard Comrie, Habitual Aspect and Progressive Aspect are sub-categories of imperfectivity. Nevertheless, it is essential to make a difference between the two. Habitual reading refers to plural events, but even so, it is not the same as accidental event plurality. The feature common to all habituals, whether or not they are also iterative, is that habituals describe a situation viewed over an extended period of time. Regarding this, Comrie also reminds that the „characteristic referred to is a characteristic feature of the whole period and not an incidental property of the moment“ (Comrie, 1976, p.27). Would and used to are the most explicit markers of habituality and are most commonly used forms to express habitualness. Simple forms are also known to have a habitual meaning, as well as the modal auxiliary can, which may occasionally convey the habitual reading as well. The matter of what exactly makes a feature characteristic for the certain period of time is in fact more conceptual than linguistic. When we manage to determine what repeated action turns out to be really habitual, we can then use explicitly habitual forms. Even then, it will be more of a conceptual matter than a linguistic one.